Effect of iron on serum vitamin D and renal vitamin D receptor expression in rats - Si-yu GU; Rui LI; Yi-min ZHAO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo investigate the effect of iron on serum 25-hydroxyvitamin D3 (25-(OH)D3), 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) and the expression of vitamin D receptor (VDR) in rat kidney. Methods With 7 days' adaptive feeding, thirty newly weaned male Sprague-Dawley (SD) rats were randomly divided into a control group (n = 6) and a model group (n = 24) according to body weight. The rats in the control group were fed with normal diet and those in the model group were fed with iron deficiency diet for 6 weeks. After successful modeling, the rats in model group were randomly divided into four group (6 rats in each group) with iron deficiency, and low, moderate and high iron according to hemoglobin (Hb) content. The rats in the control group and the iron deficiency group were given normal saline, and the rats in the low, moderate and high iron groups were given iron dextran at dosages of 11, 33 and 99 mg/kg by gastric gavage, respectively. After 4 weeks, the rats were anesthetized with 8% chloral hydrate. Blood samples of the rats were collected from the abdominal aorta for serum isolation and kidney tissue specimens were collected and stored at - 80 ℃ for later detections. Serum 25-(OH)D3 and 1,25-(OH)2D3 were detected with enzyme-linked immunosorbent assay (ELISA) kit method. Renal tissue iron content of the rats was measured with biochemical kit method. Protein expression of vitamin D receptor (VDR) in the rats' kidney was determined with Western blot and immunohistochemistry method. Results The model rats' Hb was significantly lower than that of the control rats (P < 0.05); the Hb of the rats in low, moderate and high iron groups were significantly increased compared to that of the rats in the iron deficiency group (all P < 0.05). Significantly decreased serum 25-(OH)D3/1,25-(OH)2D3 and VDR in kidney were detected in the rats of iron deficiency group contrasting to those of the rats in control group (P < 0.05 for all). In the rats of low, moderate and high iron groups, serum 25-(OH)D3 and 1,25-(OH)2D3 increased significantly (P < 0.05 for all) and with the increases of serum 25-(OH)D3 and 1,25-(OH)2D3, the VDR in kidney was gradually up-regulated in comparison with those in the rats of iron deficiency group. ConclusionIn rats, iron content affects the activation of VD3 and the expression of VDR protein in kidney.